Different plasma biomarker patterns associated with coronary atherosclerosis in low- versus high-risk individuals – an observational cross-sectional study - Cederström, Sofia; Wang, Yunzhang; Lundman, Pia; Alfredsson, Joakim; Bergström, Göran; Engström, Gunnar; Lind, Lars; Söderberg, Stefan; Tornvall, Per; Jernberg, Tomas (Atherosclerosis, 2025)
Background and aims: Targeted omics techniques can be used to identify systemic blood biomarkers associated with coronary artery disease (CAD) and cardiovascular disease (CVD) events. Our aim was to study associations between plasma protein, metabolite biomarkers and subclinical CAD in a low and a high CVD risk population. Methods: The Swedish CArdioPulmonary bioImage Study (SCAPIS) was used for inclusion of a study group without a history of atherosclerotic CVD stratified by cardiovascular risk; one low-risk group with a Systematic COronary Risk Evaluation 2 (SCORE2) of less than 5 % and one high-risk group with a SCORE2 above 7.5 %. In a cross-sectional study design, random forest and ordinal logistic regression models were used to analyse the relative importance of 409 proteins and metabolites for associations with the degree of coronary computed tomography angiography-detected subclinical coronary atherosclerosis, measured as coronary artery calcium score (CACS) and number of segments with coronary atherosclerosis (SIS) in the two groups. Results: In the low-risk group (n = 2063), branched-chain amino acids were associated with both CACS and SIS, while increased high-density lipoprotein (HDL) metabolites, with the exception of phospholipids, were associated with a lower CACS and SIS. In the high-risk group (n = 576), proteins involved in inflammatory processes showed negative associations with coronary atherosclerosis, while HDL metabolites did not show any protective effect. Renin and MMP12 were associated with subclinical CAD in both groups. Conclusions: Different plasma biomarker patterns associated with subclinical CAD (CACS and SIS) were identified in individuals with a low and a high CVD risk, which could be used to better understand protective and risk factors for CAD in primary prevention.
Keywords: Biomarkers; Coronary artery disease; Coronary computed tomography angiography; Metabolites; Risk factors